Thermo-Structural Response Prediction of UHTCC Control Surface for Hypersonic Cruise Vehicle - Narendar, Saggam; Ghori, Abdullah; Dubey, Yogita (Applied mechanics and materials, 2023)
One of the most complex issues that govern the design of a hypersonic vehicle is aerodynamic heating which is much more severe for an air-breathing vehicle as it operates within the atmosphere for longer durations. Due to the detrimental impact of aerodynamic heating on the vehicle structure, it is imperative to develop a robust thermal protection system that can protect the vehicle from high temperatures. However, the development of sophisticated TPS for slender components is impractical and, therefore, requires a hot structure system that can operate at substantial aerothermal loads. The aim of this study is to predict the impact of aero-heating on a UHTCC-based hot structure system of a hypersonic cruise vehicle through uncoupled thermo-structural analysis of the control surface. Validation of numerical methods implemented is done through literature comparison and grid independency tests.